Continuity and Change: 12 Five Year Plan (2012-2017) of Local Governments in Kerala - J.B. Rajan (KILA Journal of Local Governance, 2013)
The policy of any government depends on the political party in reign. However the policy with regard to decentralisation in Kerala is exception to this. The approach and strategy of Kerala on decentralisation since its launching during 9 th five year plan through PPC has been pro towards local governments; maintaining the continuity with appropriate changes for improvement. The guideline for 12 th Five Year Plan (FYP) of Local Governments in Kerala furthering the local planning with participatory approach but suggests for more simple and systematic process. This paper highlights striking features of the guideline with focus on continuity and change with respect to key factors.